2019
DOI: 10.1021/acscombsci.9b00099
|View full text |Cite
|
Sign up to set email alerts
|

FTO Darkening Rate as a Qualitative, High-Throughput Mapping Method for Screening Li-Ionic Conduction in Thin Solid Electrolytes

Abstract: We present a high-throughput (combinatorial) method to screen thin ceramic films as Li-ion conductors by mapping an optical effect of Li-ion conduction. The method, while qualitative, is fast and simple to implement, provides a planar (XY) map of Li-ion conductivity through different parts of the film. The effect, FTO darkening, is an optoelectrochemical one that relies on darkening of the FTO (F-doped tin oxide) substrate, onto which the investigated film is deposited. The rate of color change of the FTO refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Besides, Tirosh et al demonstrated a HT mapping method based on the F‐doped tin oxide darkening effect for screening the ionic conductivity in solid state electrolytes. [ 121 ] Each measurement requires only 5 min which is 100× faster compared with the traditional EIS method. However, the distinguishment between grain and bulk lithium ion conductivity cannot be realized.…”
Section: High‐throughput Experimentationmentioning
confidence: 99%
“…Besides, Tirosh et al demonstrated a HT mapping method based on the F‐doped tin oxide darkening effect for screening the ionic conductivity in solid state electrolytes. [ 121 ] Each measurement requires only 5 min which is 100× faster compared with the traditional EIS method. However, the distinguishment between grain and bulk lithium ion conductivity cannot be realized.…”
Section: High‐throughput Experimentationmentioning
confidence: 99%
“…We live in an era where advanced algorithms together with powerful hardware are able to predict the ionic transport of ceramic electrolytes. [137] The ability to narrow the overwhelming number of candidate materials [138,139] by computational means, such as the Materials Project, [137] constitutes a considerable advantage over the polymer or liquid electrolyte families. The high energy density of ion-conducting ceramics together with a clear understanding of the manufacturing process marks them as very promising electrolytes of the future.…”
Section: Which Of the Three Families Holds Promise?mentioning
confidence: 99%
“…8 Furthermore, it can be easily implemented as combinatorial deposition method for (1) thickness gradients by adjusting the covered area of multiple spray cycles [9][10][11][12][13][14][15] and (2) composition gradients a Energy Conversion and Hydrogen, Center for Energy, AIT Austrian Institute of by capitalizing the lateral spread of the spray cone and overlapping different precursor solutions consecutively 16 or simultanously. [17][18][19] Directly mixing multiple solutions during a laterally resolved coating process has already been reported. 20 In this contribution we synthesize combinatorial films with two-dimensional composition gradients of metal oxides.…”
Section: Introductionmentioning
confidence: 99%